(untitled) (Mongolian Journal of International Affairs, 2022)
China is a country with unique geographic position surrounded by twenty nations big and small (including Taiwan) around its periphery. China`s greatest security concern has always been a strategic encirclement – its neighbors aligning with one another or with strong powers such as the United States to isolate China. How does this sense of encirclement influence China’s strategic behavior? China`s central geographic position between Russia and the United States makes it hard for Beijing to maneuver its foreign policy in the region. Thus, China`s current leader came up with the idea of implementing a project, a modern version of the ancient Silk Road, whose specific function is to link countries of the world by the different types of infrastructure. Emerging as a feature of China`s so-called peaceful development, the Belt and Road Initiative (BRI) is a manifestation of its aspiration for connecting itself to the countries of the great Afro-Eurasian landmass by railroads, highways, shipping routes and communication networks. This article portrays the BRI as Chinese strategy of a breakout from encirclement. It argues that China is employing the BRI to pursue its strategic interests of enhancing its influence in its peripheral areas and extending its strategic reach further beyond its traditional periphery by gaining control over strategically important lands and ports.